Gênero, sexualidade e educação: um estudo feminista e fenomenológico com educadoras de uma EMEF em São Paulo - Pereira, Ana Luiza Telles (2018)
The present study starts from the demand of a municipal elementary school (EMEF), located in the north part of São Paulo, to work on the themes gender and sexuality in their daily life. Given the role of the school in the constitution of students - in the broad sense of the term, that is, in addition to the curricular contents - with the present research we sought to verify how gender and sexuality issues appear for the teachers and management team of this institution. For that, at first, we made observations of the school routine. Through the observations and meetings with the management team, we verified the need for a moment in which gender and sexuality issues could be debated. Thus, we held three meetings with the elementary school teachers and the management team. In the first meeting we worked on the concept of woman - how those teachers understood what it was to be a woman and its repercussions. In the second meeting we worked on the concept of man and masculinity, as this was a recurring subject in the first meeting. At the end of this meeting the participants asked for a more in-depth discussion on gender and sexuality, and so we planned the third meeting with them. The meetings were recorded, transcribed and analyzed in the light of existential phenomenology and feminist studies. The meetings allowed for an analysis based on two main themes: (a) Being a woman and being a man in society; and (b) Gender, Sexuality and Education. We observed that educators needed a space to discuss their own conceptions of man and woman and sexuality and how they affect their teaching practice. In addition, the meetings were marked by reports of fear regarding the reactions of families about gender and sexuality and of unpreparedness in situations considered by them as taboo. Finally, we have discussed the need for more spaces that work for diversity within the school, especially regarding the elimination of gender and sexuality prejudices